(untitled) (Bulletin KNOB, 2006)
Since 1762 the town council of Rotterdam investigated the possibility for new construction of the Delftse Poort. The gate formed an important entrance to the prosperous and sovereign town. Furthermore, the gate was used to check incoming and outgoing traffic and for the collection of municipal levies. The town council did not only pay much attention to the architecture of the building, but also to the location of the gate in the urban space. The visibility of the building within and outside the town played a significant part in this. This representative requirement had to be balanced with its practical use, the circulation of traffic. The location, which was characterised by a congestion of major roads and water ways, offering little space for a generous layout, complicated the planning process and decision making. For this important commission the town council resorted to several well-qualified advisers and experts. From the very start the architect Pieter de Swart, at that moment without doubt the most prominent architect in the Dutch Republic, was engaged as an adviser. By submitting plans and projects, private townsmen involved themselves in the decision-making. In the assessment of the various pieces of advice it turned out that it was not a matter of a hierarchy of experts in advance. In July 1765 the town council, for instance, decided to execute a beautifully painted project of the painter Adriaan van Swijndregt, although this was directly against the advice of architect De Swart. In this project the gate was built on the axis of the river Schie, so that the building would be visible from far away. De Swart considered this incompatible with the character of a land gate. Upon commencement of the construction the location on the axis of the Schie proved to be impossible from a structural point of view because of the very poor quality of the building land. On the basis of the advice obtained from a few prominent military advisers the town council opted for a new location, nearly in the same place as the old gate. In the project eventually realised the representative aspect was made subordinate to the practical possibilities, as a result of which the architecture of the building contrasted with a faulty urban location. In this article the building history of the Delftse Poort is focused on, with special attention for the various designs and projects preserved. This building history provides an insight into the range of architectural specialists who could be consulted by the local authorities in the second half of the eighteenth century.